One sky, many horizons: studies in Malaysian literature in English - Quayum, Mohammad Abdul (Marshall Cavendish International, 2014)
A collection of critical essays on Malaysian literature in English generally as well as some of the major writers in the tradition. Examines the challenges, prospects and achievements of the tradition in the last seventy years. The book has three sections. The first section has several chapters on the tradition of Malaysian writing in English. The second section has several biographical essays. Finally, there is a section comprising interviews with selected writers in the tradition